Using Baclofen to Explore GABA-B Receptor Function in Alcohol Dependence: Insights From Pharmacokinetic and Pharmacodynamic Measures - Durant, Claire F.; Paterson, Louise M.; Turton, Sam; Wilson, Susan J.; Myers, James F. M.; Muthukumaraswamy, Suresh; Venkataraman, Ashwin; Mick, Inge; Paterson, Susan; Jones, Tessa; Nahar, Limon K.; Cordero, Rosa E.; et al. (Frontiers in Psychiatry, 2018)
Background. The role of GABA-B neurotransmission in addiction has recently received increased attention, with clinical trials indicating that baclofen, a GABA-B receptor agonist, may reduce alcohol consumption, craving and promote abstinence. However, the optimal dose to treat alcohol dependence is unclear with patients requesting and tolerating much higher doses of baclofen, compared with other clinical uses. We assessed the pharmacokinetics and pharmacodynamics (PK/PD) of baclofen to provide insight into GABA-B sensitivity in this patient group, relative to controls. Methods. Male healthy volunteers (controls, n=12) and abstinent alcohol dependent individuals (AD, n=8) received single oral doses of baclofen or placebo in 3-way crossover design. Controls received placebo/10mg/60mg baclofen in a randomised, double-blind design, AD received placebo/60mg/90mg baclofen in a single-blind design. PK/PD measures were recorded at baseline and multiple time-points up to 6 hours post-dosing, including plasma baclofen, plasma growth hormone (GH), Subjective High Assessment Scale (SHAS) and biphasic alcohol effects scale (BAES). Repeated measures ANOVA analysis explored ‘change from baseline’ dose, time, group and interaction effects, t-tests compared peak effects. Results. Dose-dependent effects of baclofen on PK and PD measures were observed in both control and AD groups. Whilst there were no significant group differences in any baclofen PK parameters (T1/2, Tmax, Cmax, AUC), marked differences in PD effects were clearly evident. In controls, 60mg baclofen significantly increased total SHAS and BAES scores, and significantly increased plasma GH levels compared with placebo, with peak effects at 60 to 120mins, in line with its PK profile. In AD, 60mg baclofen had limited effects on these parameters; SHAS scores, BAES scores and plasma GH levels were significantly blunted compared with controls (significant group*time interactions P=0.0014, 0.0015 and P<0.0001 respectively). Conclusions. Our study shows blunted sensitivity to baclofen in AD relative to controls, with no difference in PK suggesting a lower GABA-B receptor sensitivity. This may explain why higher baclofen doses are requested and tolerated in the treatment of alcohol dependence. Our data has implications for choice of dose in future clinical trials in AD and possibly other substances of dependence.